Perang Tagar Di Ruang Virtual Diskursus Politik Capres Pasca Debat Putaran Kedua - Ana Fitriana P; Ema Ema; Fardiah Oktariani Lubis (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
This study aims to uncover the political discourse of the Presidential Candidates after the second round of debates, Jokowi VS Prabowo in virtual space. The background of the political discourse of the 2019 Presidential Election debate in the virtual space gave rise to various responses and sentiments among the supporters. After the Presidential Election debate, the hashtag war between #BohongLagiJokowi and # 02GagapUnicorn on social media Twitter became the main discussion. The aim is to disperse the power, ideology, and interests behind the presidential political discourse through the Fairclough Critical Discourse Analysis. The research method uses qualitative methods to parse the problem in research, using critical thinking as a basis for research. The results showed the tweet of Prabowo supporters trying to show stunts through language. The use of subject pronouns such as the word Mukidi to dwarf the subject, also uses the hashtags #DeletJokowi, #UnistallJokowi, and #BohongLagiJokowi as symbols of virtual communication. In contrast, the tweet of Jokowi's supporters sent a stuttering sentiment because they didn't understand the e-comer business. Hashtag # 02GagapUnicorn as a virtual symbol for organizing texts. In the order of messo or the production of text, the two supporters make a virtual symbol through the hashtag to become a topic of discussion on Twitter. In the situational or macro aspects are influenced by the post-truth phenomenon that is vague information whose source is unclear, have an impact on the inclusion of opinions on the assassination of certain characters. The advice, wise social media, understand and thoroughly source of information, is not affected by the use of certain metaphors, and at the stage of text, production needs to pay attention to the effects that will impact on the influence of social psychology of each supporter.Penelitian ini bertujuan untuk mengungkap diskursus politik Capres pasca debat putaran kedua, Jokowi VS Prabowo di ruang virtual. Dilatarbelakangi oleh lanskap diskursus politik debat Pilpres 2019 di ruang virtual yang menimbulkan berbagai tanggapan dan sentimen di antara kedua kubu pendukung. Pasca debat Pilpres perang tagar antara #BohongLagiJokowi dan #02GagapUnicorn di Twitter menjadi pembahasan utama. Tujuannya untuk membongkar kuasa, ideologi dan kepentingan di balik wacana politik Pilpres melalui analisis wacana kritis Fairclough. Metode penelitian menggunakan metode kualitatif untuk mengurai masalah dalam penelitian, dengan menggunakan pemikiran kritis sebagai dasar pijakan penelitian. Hasil penelitian menunjukan tweet warganet pendukung Prabowo berusaha menunjukkan pengkerdilan melalui Bahasa. Penggunaan kata ganti subjek seperti kata Mukidi untuk mengkerdilkan subjek, juga menggunakan tagar #DeletJokowi, #UninstallJokowi dan #BohongLagiJokowi sebagai simbol komunikasi virtual. Namun sebaliknya, tweet warganet pendukung Jokowi membuat sentimen dengan kata-kata gagap karena tidak memahami bisnis milenial (e-commerce). Tagar #02GagapUnicorn sebagai simbol virtual untuk pengorganisasin teks, sedangkan di tahapan produksi teks (messo) kedua pendukung membuat simbol virtual melalui tagar (#) untuk menjadi tren topik pembahasan di Twitter. Pada aspek situasional (makro) dipengaruhi oleh fenomena post-truth yaitu informasi-informasi samar yang tidak jelas sumbernya, berdampak terhadap penggiringan opini terhadap pembunuhan karakter tertentu. Sarannya, bijak bermedia sosial, pahami dan teliti sumber informasinya, tidak terpengaruh terhadap penggunaaan metafora tertentu, serta pada tahap produksi teks perlu memperhatikan efeknya yang akan berdampak pada pengaruh psikologi sosial masing-masing pendukung.